Langkah Nyata Menuju Pendidikan Berkualitas dalam Transformasi Kurikulum 2013 ke Kurikulum Merdeka di SDN Belitung Selatan 4 - Nurhanifah, Ilma; Almadani, Muhammad Seman; Maulida, Nadia; Fatimah, Siti; Pratiwi, Diani Ayu (MASALIQ, 2025)
The Merdeka Curriculum is a reform initiative in Indonesia’s education system designed to align learning processes with current educational demands and the diverse needs, interests, and potentials of students. It is considered relevant to the challenges of 21st-century education by promoting flexibility, autonomy, and differentiated learning. However, its implementation still faces several obstacles, such as limited teacher experience, lack of educational resources, and unequal access to technological infrastructure. This study aims to examine the implementation of the Merdeka Curriculum in schools and analyze the strategies adopted to overcome these challenges. Identified efforts include independent teacher training, the establishment of learning communities, improved time management in the learning process, and adaptive use of technology. The findings are expected to provide a comprehensive picture of the real dynamics of Merdeka Curriculum implementation and serve as input for its ongoing improvement.